Acid hydrolysis and microwave digestion enhanced protein extraction from red seaweed Palmaria palmata - Anushi Madushani Wijethunga; Quan Sophia He; Balakrishnan Prithiviraj; Xiaohong Sun (Food Chemistry: X)
Palmaria palmata proteins have limited dietary use due to ineffective protein extraction methods. This study explores pretreatments, including homogenization, ultrasonication, microwave digestion, surfactant addition, acid hydrolysis, and viscozyme hydrolysis, before conventional alkaline solubilization and acidic precipitation to improve protein extraction yield and purity. The results showed that microwave digestion (500 W, 30 min) and acid hydrolysis (2 M H2SO4, 95 °C, 2 h) significantly increased final yield from 10.4 ± 0.4 % to 47.6 ± 3.9 % and 46.5 ± 3.4 %, respectively. Specifically, alkaline solubilization yields reached 99.7 ± 3.7 % (microwave) and 99.2 ± 3.2 % (acid hydrolysis) (p < 0.05). Protein purity reached 89.8 ± 1.1 % with microwave digestion and 65.3 ± 1.2 % with acid hydrolysis. The protein yield increment can be attributed to effective cell wall disruption, as evidenced by SEM imaging and CLSM imaging. SDS-PAGE showed that the proteins resulting from microwave and acid hydrolysis have molecular weights below 10 kDa. This study developed effective methods with potential for scaling up to enhance protein extraction from Palmaria palmata.